High-flow nasal cannula versus non-invasive ventilation for acute exacerbations of chronic obstructive pulmonary disease with acute-moderate hypercapnic respiratory failure: a retrospective study - Colaianni-Alfonso, Nicolás; Toledo, Ada; Montiel, Guillermo; Deana, Cristian; Vetrugno, Luigi; Castro-Sayat, Mauro (Frontiers in Medicine, 2025)
BackgroundAcute exacerbations of chronic obstructive pulmonary disease (AECOPD) frequently present with acute hypercapnic respiratory failure (AHRF). While non-invasive ventilation (NIV) remains the fist-line therapy, high-flow nasal cannula (HFNC) offers a potential alternative.MethodsThis retrospective cohort study compared the clinical effectiveness and safety of HFNC versus NIV as initial respiratory support in 100 consecutive patients with AECOPD and AHRF (PaCO2 > 45 mmHg, pH 7.25–7.35). Patients were categorized into HFNC and NIV groups based on the respiratory support initiated within the first 2 h of admission. The primary outcome was treatment failure, defined as intubation, switch from one non-invasive respiratory support to another or death under NIRS. Secondary outcomes included respiratory rate (RR), arterial blood gas parameters, length of stay, and duration of respiratory support.ResultsTreatment failure rates were comparable between the HFNC (32%) and NIV (35%) groups (p = 0.72). However, reasons for treatment escalation differed significantly. NIV failure was largely due to intolerance, while HFNC failure was associated with worsening respiratory distress or hypercapnia. NIV demonstrated superior early improvements in RR and PaCO2 compared to HFNC. No statistically significant differences were found in length of stay or 28-day mortality.ConclusionThis study suggests similar overall treatment success rates for HFNC and NIV in AECOPD with AHRF. However, NIV appears more effective in achieving early respiratory improvements, whereas HFNC offers superior tolerability. Further large-scale, prospective, randomized controlled trials are warranted to definitively establish optimal respiratory support strategies for this patient population.